Adrenaline Rush: The Role of Adrenergic Receptors in Stimulant-Induced Behaviors - Schmidt, Karl T. (The American Society for Pharmacology and Experimental Therapeutics, 2014)
Psychostimulants, such as cocaine and amphetamines, act primarily through the monoamine neurotransmitters dopamine (DA), norepinephrine, and serotonin. Although stimulant addiction research has largely focused on DA, medication development efforts targeting the dopaminergic system have thus far been unsuccessful, leading to alternative strategies aimed at abating stimulant abuse. Noradrenergic compounds have shown promise in altering the behavioral effects of stimulants in rodents, nonhuman primates, and humans. In this review, we discuss the contribution of each adrenergic receptor (AR) subtype (α1, α2, and β) to five stimulant-induced behaviors relevant to addiction: locomotor activity, conditioned place preference, anxiety, discrimination, and self-administration. AR manipulation has diverse effects on these behaviors; each subtype profoundly influences outcomes in some paradigms but is inconsequential in others. The functional neuroanatomy and intracellular signaling mechanisms underlying the impact of AR activation/blockade on these behaviors remain largely unknown, presenting a new frontier for research on psychostimulant–AR interactions.